Mini Drone Linear and Nonlinear Controller System Design and Analyzing - Esraa Hadi Kadhim; Ahmad T. Abdulsadda (Journal of Robotics and Control (JRC), 2022)
Choosing the mini-drone for a specific payload for designing purposes is one of the most challenging for both cost and design purposes. It is important to develop and analyze the flight control systems of the quadcopter-type Parrot mini drone and how to make the drones more tolerant of adverse weather conditions. The main problem with any quadcopter is that it loses its balance when exposed to any external influence, even if that influence is weak. Where the controller is the most important part of the drone, six plane controllers cover the six degrees of freedom (6dof) in the movement of the drone. In our research, we have improved the height controller in the drone, thus improving the altitude controller by using (PD) and increasing the values of (Kp and Kd) in the altitude controller of the Parrot Mini Drone Mambo to make it more bearable to external influence and to maintain its altitude. We assumed that the aircraft was exposed to bad weather conditions, such as snowfall and dust, which led to an increase in the speed at which the drone fell. We also increased the free fall constant of the object in the simulation design of the drone from (-9.81 m/s2 to -12.81 m/s2) and used Matlab R2021a Simulink to undertake the tuning of the (Kp and Kd) values. This study yielded good results, as illustrated in the results section. Therefore, this research paper suggests adopting the PD controller in the altitude controller and the new values of Kp and Kd to make the drone more tolerant of weather conditions. We tested these results in practice and got good results.